2019
DOI: 10.3390/ijerph16214173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anxiety and Depression in Polish Primary Parental Caregivers of Children with Cerebral Palsy Compared to a Control Group, as well as Identification of Selected Predictors

Abstract: Background: Taking care of a child with Cerebral Palsy (CP) may be linked with adverse effects in the parents’ physical and mental health. The causes of anxiety and depression symptoms associated with childcare are still not fully understood. Aim: To assess the intensity of anxiety and depression symptoms in parents of children with CP compared to a control group and to identify selected mental health predictors. Design and Methods: Data were collected from 301 respondents, including 190 parents of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 52 publications
2
19
1
2
Order By: Relevance
“…Due to the specificity of the Caregiver Burden Scale (CBS) as a research tool, caregiver burden was not assessed in the parents of healthy children. 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the specificity of the Caregiver Burden Scale (CBS) as a research tool, caregiver burden was not assessed in the parents of healthy children. 12 …”
Section: Methodsmentioning
confidence: 99%
“…Such excessive care-related responsibilities may adversely affect the parents' physical and mental health, as well as their social, cultural and professional life. [6][7][8][9][10][11][12][13] In the literature excessive caregiver burden is presented as a multidimensional problem, or a combination of objective and subjective characteristics. These include physical issues-mainly linked with the affected child's functional condition; mental aspects-connected with the parent's ability to cope with a stressful situation of managing a child with a disorder; social problems-reflected in the parent's relations with other people and financial difficulties-linked to the parent's discontinued employment, as well as costs of the child's treatment and rehabilitation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, comparative research between Canadian parents who do or do not care for a child with CP found that caregiving was associated with more chronic conditions, including back problems, migraines/headaches, and stomach/intestinal ulcers (Brehaut et al, 2004). Other researchers have suggested that parents who care for a child with CP experiences significantly more psychological problems, such as increased stress and depression, than parents of typically developing children (Butcher et al, 2008; Gugała et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…de participação em eventos sociais, falta de apoio do cônjuge e da família, estresse, dificuldades de conciliar o trabalho fora de casa e sobrecarga financeira relacionada aos gastos com medicamentos, transporte e equipamentos, porém, além somente dos sentimentos negativos, algumas mães relataram também uma maior capacidade de aceitação referente ao diagnóstico. Já em relação as barreiras encontradas, foram comuns as queixas relacionadas a carência de acessibilidade para pessoas com deficiências, principalmente a falta de transportes e locais públicos acessíveis e inclusivos.Ao comparar os níveis de sobrecarga e depressão em pais de crianças com PC e pais de crianças saudáveis,Gugala et al (2019) verificaram que esses níveis foram significativamente maiores no grupo de pais de crianças com PC. Os preditores de ansiedade QV dos cuidadores, sugerindo possíveis ações de atenção voltadas para essa população, porém, ainda há poucos estudos que retratem sobre essas ações.…”
unclassified